Изменение рельефа поверхности магния под действием мощных потоков ионов углерода - Потемкин Г. В. Гелий Валерьянович; Лигачев А. Е.; Жидков М. В.; Колобов Ю. P.; Ремнев Г. Е. Геннадий Ефимович; Смолякова М. Ю.; Божко С. А. (2014, 2014)
Заглавие с экрана